From the centre to periphery: The Middle Eastern impacts on Islamic education in Indonesia - Pradana Boy ZTF (Journal of Social Studies (JSS), 2020)
This paper traces Middle Eastern elements in Islamic education in Indonesia by looking at their institutions, curricula, method of teaching, orientations, and Islamic ideological transmission. The information on values and impacts of Indonesian and Middle Eastern Islam takes a one-way traffic pattern in general terms. The dynamics of Islam in Middle Eastern regions will fundamentally affect the practice and dynamic of Islam in Indonesia. This paper maps out Middle Eastern components' influence on the course of education run by these two largest Islamic organizations in Indonesia, Muhammadiyah and Nahdlatul Ulama'. However, following the New Order's fall, many Islamic groups emerged; education offered by these new groups and orientations is also worthy of evaluation. In the modernist group, the idea and practice of Islamic reform, which constitutes one of its significant agendas, mostly echoed the similar and earlier movements in the Middle East. Similarly, traditionalist groups are often described as the revivers of more locally-rooted Islamic practice, and therefore, they tend to blend local and Middle Eastern elements within their religious way.